2022
DOI: 10.4081/jphr.2021.2346
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarettes Consumption and Associated Factors among General Population in Western Saudi Arabia

Abstract: Background: In recent years, consumption of E-cigarettes has increased dramatically. Several studies have focused on the prevalence of E-cigarettes among specific groups of people, using it as a substitute to traditional cigarettes, or the participant knowledge regarding risks. This research was aimed on E-cigarettes’ prevalence and its association to several factors in the general population of Western Saudi Arabia.Design and Methods: Using an observational cross-sectional study, data were collected from (n=4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 30 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…In addition, most of the participants were young. In addition, most studies reported that social media are the main source of information related to e-cigarette use 21,24,27,28,32,39,41,43,47,51,88 . Furthermore, most of the studies used electronic questionnaires, thus, respondents would be participants who have access to the Internet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, most of the participants were young. In addition, most studies reported that social media are the main source of information related to e-cigarette use 21,24,27,28,32,39,41,43,47,51,88 . Furthermore, most of the studies used electronic questionnaires, thus, respondents would be participants who have access to the Internet.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies (n=17) included in this review were conducted in Saudi Arabia [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]55 . The first study was conducted in 2014 (participants, n=3027).…”
Section: Prevalence and Awareness Of E-cigarettes In Arab Countries S...mentioning
confidence: 99%
See 2 more Smart Citations
“…In Europe, the prevalence of EC use among young adults increased from 7.2 to 15% in 2017 ( 15 , 16 ). In the Middle East, despite the wide range of prevalence, a recent study conducted on the general population in Jeddah, Saudi Arabia showed an increased rate of 51.4%, with the majority being high school and college students ( 17 ).…”
Section: Introductionmentioning
confidence: 99%